A survey on issues and needs of recreational public spaces in Kuala Lumpur - Mansor, Mazlina; Ghani, Nurfaezah; Zakariya, Khalilah; Harun, Nor Zalina (Pusat Pengajian Ilmu Kemanusiaan, 2017)
Public recreational parks and open spaces in Kuala Lumpur are provided to support leisure activities of city residents, including voluntary, recreation and social activities. The public spaces play a positive reinforcement in promoting a healthy lifestyle for the residents. They are the places that can contribute to city residents’ health, physically, mentally and socially. Nonetheless, it is implied that Malaysia has not yet achieved a satisfactory degree of public space planning, design and development of recreational areas in order to facilitate residents with a healthy environment. The study investigates city residents’ use and needs of public recreational parks and open spaces in Kuala Lumpur. The parameters such as issues, types of activities needed and quality of the public recreational parks were investigated. Survey results from 1500 respondents who live in the areas of Kuala Lumpur City Center, Wangsa Maju-Maluri and Sentul-Manjalara strategic zones were obtained. The respondents’ answers were statistically analyzed using the SPSS software. The findings will reveal leisure time behavior of residents in Kuala Lumpur, and places that fulfill their acquisition for a healthy lifestyle. Furthermore, the findings will suggest pertinent issues on the recreational spaces, and what residents actually require of the recreation areas. This is useful for evaluating future needs on the city’s public recreational spaces and the physical environment that can cater activities that affect city residents’ health.